2021
DOI: 10.3390/magnetochemistry7020026
|View full text |Cite
|
Sign up to set email alerts
|

Geometrically Constrained Skyrmions

Abstract: Skyrmions are chiral swirling magnetization structures with nanoscale size. These structures have attracted considerable attention due to their topological stability and promising applicability in nanodevices, since they can be displaced with spin-polarized currents. However, for the comprehensive implementation of skyrmions in devices, it is imperative to also attain control over their geometrical position. Here we show that, through thickness modulations introduced in the host material, it is possible to con… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…These skyrmions are resilient against external stray magnetic fields and possess velocities, which are much higher than their ferromagnetic counterparts, making them good candidates for elementary building blocks in storage and logic. In addition to using magnetic configurations with zero topological charge, SKHE can also be suppressed with different confinement techniques [24][25][26][27][28][29]. In particular, we have shown that skyrmion channels can be defined by a local modification of the magnetic properties using light ion irradiation.…”
Section: Introductionmentioning
confidence: 94%
“…These skyrmions are resilient against external stray magnetic fields and possess velocities, which are much higher than their ferromagnetic counterparts, making them good candidates for elementary building blocks in storage and logic. In addition to using magnetic configurations with zero topological charge, SKHE can also be suppressed with different confinement techniques [24][25][26][27][28][29]. In particular, we have shown that skyrmion channels can be defined by a local modification of the magnetic properties using light ion irradiation.…”
Section: Introductionmentioning
confidence: 94%
“…Their non-trivial topology, small size and ultralow driving force make them promising information carriers [8][9][10][11][12][13][14][15][16][17][18][19][20][21]. Similar to the importance of magnetic domain wall (DW) pinning [22] in DWbased devices, skyrmion pinning by disorders and intentionally created nano-structures is important in skyrmionics [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. Skyrmion pinning in nano-structures with different exchange stiffness, or DMI strength, or magnetic anisotropy, or saturation magnetization has been investigated [10,[26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Skyrmion pinning in nano-structures with different exchange stiffness, or DMI strength, or magnetic anisotropy, or saturation magnetization has been investigated [10,[26][27][28][29]. Skyrmion pinning by atomistic spin vacancies or geometrical constrains like film thickness modulations and semicircular notches at lateral boundaries has also been studied [29][30][31]. It was found [29] that pinning by a small structure can occur at or away from the center of a nano-structure.…”
Section: Introductionmentioning
confidence: 99%
“…Previous attempts to control the localization of skyrmions include structural patterning of the magnetic film with notches ,, and discs as well as the introduction of defects , and nanopockets to define positions for skyrmion nucleation. However, all of these methods include significant structural or even geometrical modifications of the magnetic racetrack and render an unhampered motion of the skyrmion after creation difficult.…”
mentioning
confidence: 99%